Mass spectrometry—A versatile tool for characterising the lipid environment of membrane protein assemblies. (July 2019) - Frick, Melissa; Schmidt, Carla
Graphical abstract: Highlights: The organization of biological membranes is affected by the protein and lipid composition. Mass spectrometry is well-suited to identify lipids in biological membranes. Mass spectrometry provides insights into lipid binding to membrane proteins and helps unravelling the binding modes. Membrane mimics for studying membrane proteins in a native-like lipid environment are available. Membrane mimics are compatible with mass spectrometry. Abstract: Biological membranes are selectively permeable barriers important for cell organization and compartmentalization. Their organisation strongly depends on the lipids that constitute the lipid bilayer as well as the proteins that reside in the membrane. Unravelling the organisation of biological membranes is therefore of great importance to understand cellular function driven by integral and peripheral membrane proteins. Recent developments in mass spectrometry made it a powerful tool contributing to our present-day understanding of membrane composition and organisation. The two main deliverables of mass spectrometry are (i) the identification and quantification of the membrane components, and (ii) the analysis of their structural arrangements. In this review article, we first briefly discuss the aspects of membrane organization that are accessible through mass spectrometry. We then provide detailed insights into the various mass spectrometric strategies which help identifying lipids from membranes or membrane protein assemblies, unravelling the lipid binding modes in membrane proteins and uncovering their structural roles. We further discuss the growing interest in membrane mimetics providing membrane proteins with a native-like lipid environment for structural and functional studies and the possibilities of mass spectrometry to contribute in these experiments.